1992
DOI: 10.1111/j.1365-2621.1992.tb08063.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Inclusion Complexes of Cyclodextrins with Triglyceride at Vegetable Oil/Water Interface

Abstract: The interfacial tension of vegetable oil (soybean oil or coconut oil)/ water interface decreased with the increase of cyclodextrin (CD) concentration. The interfacial excess and interfacial area were calculated from the Gibbs' adsorption equation. The average number of CD molecules including a fatty acid residue of soybean oil at the interface was estimated at 2.4 for each of a-CD and S-CD. The average number of CD molecules complexed with a fatty acid residue of coconut oil was 1.8 for a-CD and 1.7 for S-CD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 6 publications
2
33
0
3
Order By: Relevance
“…Schematic presentation of the successive steps involved in beads preparation is presented in Figure 1. The preparation process involves the addition of oil to CD aqueous solution which results in the formation of two non-miscible phases separated at the oil/water interface by a macroscopically visualized self-forming film (Shimada et al, 1992). For a-CD and soybean oil combination, the latter is composed of partial inclusion complexes of a-CD molecules with TGs (Shimada et al, 1992;Bochot et al, 2007).…”
Section: Beads Preparation and Drug Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…Schematic presentation of the successive steps involved in beads preparation is presented in Figure 1. The preparation process involves the addition of oil to CD aqueous solution which results in the formation of two non-miscible phases separated at the oil/water interface by a macroscopically visualized self-forming film (Shimada et al, 1992). For a-CD and soybean oil combination, the latter is composed of partial inclusion complexes of a-CD molecules with TGs (Shimada et al, 1992;Bochot et al, 2007).…”
Section: Beads Preparation and Drug Loadingmentioning
confidence: 99%
“…The preparation process involves the addition of oil to CD aqueous solution which results in the formation of two non-miscible phases separated at the oil/water interface by a macroscopically visualized self-forming film (Shimada et al, 1992). For a-CD and soybean oil combination, the latter is composed of partial inclusion complexes of a-CD molecules with TGs (Shimada et al, 1992;Bochot et al, 2007). This partial inclusion complex constitutes a surface-active agent (hydrophilic head and a hydrophobic tail) with amphiphilic property where a-CD containing the FA chain being oriented toward the aqueous phase while the two remaining free FA chains are oriented toward the oily phase (Shimada et al, 1992;Duchêne et al, 2003).…”
Section: Beads Preparation and Drug Loadingmentioning
confidence: 99%
“…Assim se obtém α, β, e γ-ciclodextrinas e pequenas quantidades de outras dextrinas (6,13,16,23, 29,38, 46), sendo a β-ciclodextrina a de maior aplicação industrial. As ciclodextrinas α, β e γ podem ser facilmente separadas do conteúdo desta reação por precipitação seletiva, mediante adição de determinados solventes orgânicos.…”
Section: Introductionunclassified
“…As ciclodextrinas apresentam cavidade hidrofóbica de dimensões médias (1,5 nm x 0,7 nm x 0,8 nm) e superfície hidrofílica, devido a presença de grupos OH. Esta estrutura permite a formação de complexos de inclusão estáveis, com grande diversidade de substâncias orgânicas, sais e halogênios (13,14,23,29,34,38), além de formar complexos com substâncias de massa molecular típica de 80 a 250 Daltons (6, 24). Compostos hidrófobos de cadeias longas formam complexos mais fortes do que compostos hidrofílicos de cadeias curtas (16,24,29).…”
Section: Introductionunclassified
“…1) However, there are a few reports on the use of CD as an emulsifier. Only the emulsification of fatty acid using CDs by Shimada et al 2,3) and the preparation of O/W/O-type multiple emulsion using CDs by Yu et al 4,5) have been reported. Moreover, the mechanism of emulsion formation using CD has not been sufficiently investigated.…”
mentioning
confidence: 99%